1984
DOI: 10.1088/0022-3727/17/2/017
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility calculations for mercury-argon low pressure gas discharges

Abstract: A new formula is derived which gives electron mobility values in argon in good agreement with experiment and calculation. The effect of mercury on electron mobility in argon is expressed as a correction factor. The theoretical expression obtained is applied to discharge conditions for which exact results are known, and the results are compared. The values of mu e obtained have been used to calculate axial electron density, showing good agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…43 A matched asymptotic analysis of plasma sheath behavior showed that the maximum current density J transitions from CL scaling, J / V 3=2 =D 2 , to MG scaling, J / V 2 =D 3 , by incorporating electron mobility l, defined as v d ¼ lE, where v d is the drift velocity and E is the electric field, into the fluid equation for electron motion. 44 Thus, asymptotic studies have demonstrated the transition from FN to CL 17 and CL to MG; 45 however, no study has comprehensively assessed the transition between all three electron emission mechanisms. Given the necessity of incorporating collisions into electron emission theory for either D % k at atmospheric pressure or SCLE for imperfect vacuum, this letter assesses the transitions between FN, MG, and CL by including electron mobility into the equation for electron motion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…43 A matched asymptotic analysis of plasma sheath behavior showed that the maximum current density J transitions from CL scaling, J / V 3=2 =D 2 , to MG scaling, J / V 2 =D 3 , by incorporating electron mobility l, defined as v d ¼ lE, where v d is the drift velocity and E is the electric field, into the fluid equation for electron motion. 44 Thus, asymptotic studies have demonstrated the transition from FN to CL 17 and CL to MG; 45 however, no study has comprehensively assessed the transition between all three electron emission mechanisms. Given the necessity of incorporating collisions into electron emission theory for either D % k at atmospheric pressure or SCLE for imperfect vacuum, this letter assesses the transitions between FN, MG, and CL by including electron mobility into the equation for electron motion.…”
mentioning
confidence: 99%
“…We start with a one-dimensional, planar diode with the cathode at x ¼ 0 and the anode at x ¼ D, fixed at V with respect to the cathode. The gap is filled with a neutral gas with electron mobility l, which varies inversely with pressure P. 45 We assume electron emission from the cathode with negligible initial (t ¼ 0) velocity and accelerated by the surface electric field E s ¼ E(0), or x 0 ð Þ ¼ 0; v 0 ð Þ ¼ 0; a 0 ð Þ ¼ eE s =m. Coupling Poisson's equation with continuity, J ¼ env, where e, n, and v are the electron charge, number density, and velocity, respectively, yields…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estimations show that, under the discharge conditions in question, this model must include the birth of charged particles due to collisions of excited mercury atoms [17]. The roles of other processes which could manifest themselves under the higher pressure of gases, namely, the influence of elastic collisions between electrons and mercury atoms on the electron mobility [18] and the influence of elastic collisions between electrons and inert gas atoms on the electron energy balance, are unimportant. For instance, in the case of 'classical' luminescent lamps, according to [18], the first process has to be taken into account at the mercury vapour pressure corresponding to the temperature of a mercury bath T Hg > 60 • C. The essentially higher pressure of a rare gas in compact luminescent lamps makes it possible not to take into consideration elastic collisions between electrons and mercury atoms up to T Hg = 80 • C. The second processelastic collisions between electrons and rare gas atomsand its influence on the electron energy balance are, as estimation shows, inessential for a (Hg + Ar) discharge plasma at p Ar < 30 Torr and N 0 > 2 × 10 14 cm −3 (T Hg > 40 • C).…”
Section: The Theoretical Model Similarity Of the Discharges And Its U...mentioning
confidence: 99%
“…The electric current equation is where ,u,(r) denotes the electron mobility in a mixture of mercury and argon. We adopted here the expression of pe given by Chen and Jones (1984).…”
Section: A Theoretical Modelmentioning
confidence: 99%